Highly efficient electrochemical recognition and quantification of amine enantiomers based on a guest-free homochiral MOF. Issue 19 (16th February 2017) - Kuang, Rui; Zheng, Luyi; Chi, Yanhui; Shi, Jingmin; Chen, Xuexue; Zhang, Chengcheng
Abstract : A novel homochiral MOF was facilely synthesized, its nanocrystals exhibit rapid discrimination of α-methylbenzylamine enantiomers and quantitative determination of enantiomeric excess. Abstract : We facilely synthesized a novel guest-free homochiral metal–organic framework, (Cu4 L4 ) n [H2 L = N -(2-hydroxybenzyl)-l -leucine] in space group P 1. The (Cu4 L4 ) n nanocrystals exhibit high electrochemical activity for rapidly discriminating chiral α-methylbenzylamine enantiomers and quantitatively determining the enantiomeric excess in the chiral amine mixture.